Processing Method for Metallic Substrate Using the Liquid Metal Lapping-Polishing Plate - Ji, Renquan; Zhang, Liyang; Zhang, Li; Li, Yanbiao; Lu, Shasha; Fu, Yufei (Frontiers in Materials, 2022)
Metal is the primary substrate for fabricating flexible sensors, and its surface quality has a significant effect on the performance of these sensors. The traditional lapping-polishing technology has the disadvantages of being time-consuming and presenting difficulty in controlling the uniformity. In this paper, a liquid metal lapping-polishing plate with a self-shaping function is proposed and developed, which can realize high quality and low surface damage in the processing of the metallic substrate. It is found from the fundaments of the liquid metal lapping-polishing plate that the temperature generated by the friction between the workpiece and plate plays an important role in affecting the processing performance, and then a numerical study of the temperature field on the liquid metal lapping-polishing plate surface has been carried out, and it is found that the temperature increase with the increment of the pressure and rotation speed of the lapping-polishing plate on the target surface. Finally, it is found from experiments that the experimental results have shown to be in good agreement with the corresponding experimental data for the highest temperature under specific conditions and the processing performance has been significantly improved as well.